Second Summit of the Peoples of America. Declaration of the ASC on the FTAA, April 2001 - Social Continental, Alianza (2016)
The Continental Social Alliance had its beginnings in the Third Trade Union Summit parallel to the FTAA Ministerial Meeting, held on May 12 and 13, 1997 in Belo Horizonte. In that meeting, a group of union and social organizations issued a Joint Declaration that expressed demands and clear proposals against the FTAA. Almost four years since the publication of that Declaration, and after repeated initiatives in several countries to demand an agreement whose main objective is to promote an equitable and sustainable development, everything indicates that these demands have been completely ignored.